Development of cell-based immunoassays to measure type I collagen in cultured fibroblasts - Jones, Brian; Bucks, Christine; Wilkinson, Patrick; Pratta, Michael; Farrell, Francis; Sivakumar, Pitchumani (The international journal of biochemistry & cell biology, 2010)
Excessive deposition of type I collagen by activated fibroblasts is a hallmark of scarring and fibrotic pathologies. Quantitation of collagen I at the protein level is paramount to measure functionally relevant changes during pathological remodeling of the extracellular matrix. We describe two new cell-based assays to directly quantify the amount of collagen I incorporated into the extracellular matrix of primary human lung fibroblasts. Utilizing a monoclonal antibody specific to native human collagen I, we optimized conditions and parameters including incubation time, specificity and cell density to demonstrate dose-dependent induction of collagen I by transforming growth factor beta, as measured by in-cell enzyme linked immunosorbent assay. The results obtained by this assay were mimicked by an “In situ Quantitative Western Blot” on cultured cells using the same antibody. Results from these assays were comparable to those obtained with a commercial assay for collagen I N-propeptide, which is an index of collagen formation. These assays have been optimized for a 96-well format and provide a novel and useful approach for screening of anti-fibrotic agents in vitro. The assays described here also offer a significant improvement in throughput and specificity over conventional methods that primarily measure soluble collagen.